(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Laboratory studies were conducted to evaluate the efficacy ofaqueous and organic extracts of the argel (S. argel) shoots against the 4thlarval instar and adult stages of the red flour beetle (Tribolium castaneum)in the Sudan. Argel shoots were extracted sequentially by organic solventsof increasing polarity (petroleum ether, ethyl acetate and ethanol) as wellas directly by distilled water or ethanol. Extracts were tested atconcentrations ranging between 1% and 10%. The evaluated efficacyparameters were mortality, repellency and antifeedant effects. The testswere conducted in Petri dishes (9 cm i.d) and plastic cups (capacity 200ml) and the obtained data were subjected to the analysis of variance and tothe probit analysis. The results of the mortality data indicated thatpetroleum ether extracts was the most potent against the 4 th larval instar ofT.castaneum as shown by its low LD50 of 8.2%, while ethyl acetateextract was the most potent against the adult of this pest with an LD50value of 16%. The results showed that various types of argel shootextracts induced significant dose dependent repellency against theT. castaneum. The highest 24 hours repellency was caused by thepetroleum ether extract on the adult stage of T. castaneum as indicated byits low ED50 value of 1.58%.The different argel shoot extracts inducedsignificant antifeedant action against the test insect. The lowest feedingratio (0.02) was recorded in ethyl acetate extract- treated crushed wheatgrains